When is Subnational, Supralocal Tobacco Control "just right"? A Qualitative Study in England. Issue 8 (14th March 2022) - Davies, Nathan Philip; Cheeseman, Hazel; Arnott, Deborah; Pierce, Elizabeth; Langley, Tessa Elizabeth; Murray, Rachael; Bogdanovica, Ilze; Bains, Manpreet
Abstract: Introduction: Subnational, supralocal (or "regional") approaches to tobacco control are often central federal nation tobacco control and can be superfluous for very small nations. However, their relevance to countries with weak intermediate tiers of governance are less clear. This study explores expert and policymaker perceptions on the function, form, footprint, and funding of regional tobacco control (RTC) in England. Aims and Methods: One-to-one semistructured interviews ( n = 16) and four focus groups ( n = 26) exploring knowledge and perceptions of the past, present, and future of RTC in England were conducted with public health leaders, clinicians, tobacco control practitioners, civil servants, and politicians. Interviews were audio-recorded, transcribed verbatim, and analyzed thematically. Results: Participants reported several key functions for RTC, including illicit tobacco control, media campaigns, advocacy, policy development, and network facilitation for local actors. A small minority of participants reported little role for RTC. Broader perceived features of effective RTC included subject expertise, strong regional ties, systems leadership, and a distinctive program of work. Views varied on whether regional programs should be developed nationally or locally, and their optimal footprint. Participants generally agreed stable funding was a prerequisite for success, although there was lesser agreement on funding sources. Conclusions: Pooling resources at the regional level in countries with weak intermediate tiers of governance may increase reach, cost-effectiveness and impact of campaigns, policy interventions, and advocacy, whilst retaining the ability to tailor approaches to regional populations. Implications: There are likely to be greater funding and governance challenges associated with introducing or strengthening RTC in countries with weak intermediate tiers of governance. Despite this, evidence from England shows it is possible to develop RTC approaches reported as effective by key stakeholders. Possible benefits of regional approaches in this context include cost-effective delivery of illicit tobacco control, media campaigns, advocacy, research, policy development, and coordinated support for local action on tobacco.